Assessing Social Relationship and Network Strength among Sports Organizations and Athletes: A Study on Rajshahi City Corporation - Tawfiqush Shalahin Tushar; A.K.M. Mahmudul Haque; Imran Hossain (Khazanah Sosial, 2024)
In countries like Bangladesh, people often do not consider sports as a viable career option, which is why they tend to avoid it. However, nowadays people are becoming more advanced in both body and mind. In this scenario, the level of social interaction should increase between sports organizations and athletes. The aim of this study is to examine the level of relationship between sports organizations and athletes through empirical research that uses both qualitative and quantitative data. The researchers have collected primary data through face-to-face interviews and focus group discussions from a sample of 102 individuals, including 91 athletes and 11 club authorities. The main outcome of this research is that many social development initiatives were undertaken by sports organizations, which brought all the athletes together and formed an incredible social relationship among them.